The Evolving Role of Erythropoietin in Lung of Irradiated Rats - Ashry,Omaima Mohamed (2017)
ABSTRACT The aim of the present study is to evaluate the possible curative effect of erythropoietin (EPO) on radiation-induced damage to the lung and its renin angiotensin system. EPO (200 U/100g) was i.p. injected to male rats one hour post 6 Gy whole body gamma irradiation. The animals were sacrificed after 14 days post irradiation. Irradiation induced significant drop of haematological values, bone marrow (BM) count, lung oxidative stress markers, glutathione (GSH) and superoxide dismutase(SOD) associated with significant elevation of malondialdehyde (MDA), advanced oxidation protein product (AOPP) and nitric oxide (NO) besides serum inflammatory markers, tumor necrosis factor alpha (TNF-α) and lactate dehydrogenase (LDH). Also serum and lung renin angiotensin system markers, sodium (Na) and potassium (K) were elevated whereas calcium (Ca) was decreased. EPO treatment post irradiation has significantly ameliorated blood parameters and BM count also lung oxidative stress markers were improved associated with decreased serum Na, TNF-α, and LDH levels. Lung K and Ca showed no change compared to irradiated group. The findings of the present study suggest that EPO might contribute to enhance recovery of the lungs from radiation-induced damage due to its erythropoietic, anti-oxidative and anti-inflammatory effects.